Analysis of User Experience (Ux) of Serif and Sans Serif Fonts in Dark Mode Website Display - Satheno, Gabriel Christian Ilham; Frobenius, Arvin Claudy (Jurnal Sosial Teknologi, 2025)
The main purpose of this study is to find out the perception of user experience of two types of fonts, namely serif and sans serif in dark mode display. The variables tested were visual comfort, eye comfort and visual preferences of the user himself. The research process involved forty participants who were determined based on criteria. The method used is qualitative which aims to analyze the results of the data in detail and in-depth and the evaluation method using Thematic Analysis which aims to identify recurring patterns, group answers based on themes that arise and interpret the meaning of these themes. After testing the data analysis using Thematic Analysis, the findings of this study stated that there are four main points, namely sans serif fonts are predominantly chosen because they provide higher visual comfort, serif fonts although considered aesthetically pleasing but considered disruptive in digital readability, especially in dark mode, most prefer dark mode but the effectiveness of its use is highly dependent on the contrast setting between the background and the color of the text, and simple, organized, and not visually redundant layouts and visual structures tend to increase reading duration and encourage user engagement. On the other hand, a dense or element-packed design distracts concentration and makes users leave the page faster.